Teachers’ Perspectives on Private Education: Meritocratic (In)Equality of Opportunity in the Context of Neoliberalism - Stirbinskas, Stasys (Sociologija. Mintis ir veiksmas, 2025)
The meritocratic system, grounded in individual achievement and the principle of equality of opportunity, seeks to promote social mobility through education. In Lithuania, however, private educational practices that contradict this principle have become increasingly widespread. Drawing on semi-structured interviews with 17 teachers in the compulsory formal education system, this article examines how private educational practices relate to equality of opportunity within a neoliberal context, aiming to reveal the ideological compatibilities and contradictions between these phenomena. Teachers’ perspectives indicate that private education embodies key features of neoliberal economization, including the display of high social status linked to the accumulation of human capital, a formally increasing freedom of choice, intensified competition, the spread of marketing practices, and the promise of higher educational quality. Yet, their attitudes also highlight a fundamental contradiction: the expansion of educational privatization fosters social inequality, diminishes the prestige of public education, and leads to unequal fulfillment of educational needs. This undermines the pursuit of equality of opportunity. In theoretical terms, these findings suggest that meritocracy, shaped in the post-war welfare state era, and neoliberalism may be incompatible, as neoliberalism undermines the conditions necessary for realizing equality of opportunity, rendering the principle largely declarative.